SUMBANGAN WANITA NELAYAN DALAM PENINGKATAN PENDAPATAN KELUARGA - Sri Wahyuningsih; Aniya Widiyani'; Ismiyatun Ismiyatun (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
The research was case study in Tambak Lorok village, sub district Tanjung Mas, North Semarang District, Semarang City. The goal of this research is know about types processing of fisherman catching and their technologies, many problems of fisher women on their economic activity as an employer of the processing of fishcnnan catching, their time allocation for the activity, their sharing on family income improvement and the correlation between the role of fisher women on family income improvement with their role on community social function. This research used primary and secondary data. Analyses for proofing of processing taking time more than the other times, and used test. For correlation between time allocation on processing catching with their sharing on family income, was used correlation analysis. For testing correlation between the women sharing on family income improvement with their role on community social function was used analysis simple correlation. The research yield that types of processing included of: salted fish, baked fish, terrace and peels of cockle shells. Processing technology that was used could be categorized as traditional technology. The problem ofthe women on this processing were investment, basic ingredient and technology. The time that was used by the fisher women of the processing was longer than the other or non processing activity. The longer the time was used, the bigger the share of this women on total family income. There is no correlation between the share on improvement family income with the role on community social function.